Clinical Research Network: JHCRN Infrastructure and Lessons Learned - Rahul Kashyap; Gayane Yenokyan; Robert Joyner; Melissa Gerstenhaber; Mary Alderfer; Erika Siegrist; Joan Moore; Channing J. Paller; Hanan Aboumatar; James J. Potter; Stanley Watkins Jr; John E. Niederhuber; et al. (Clinical and Translational Science)
ABSTRACT Clinical research studies are becoming increasingly complex resulting in compounded work burden and longer study cycle times, each fueling runaway costs. The impact of protocol complexity often results in inadequate recruitment and insufficient sample sizes, which challenges validity and generalizability. Understanding the need to provide an alternative model to engage researchers and sponsors and bringing clinical research opportunities to the broader community, clinical research networks (CRN) have been proposed and initiated in the United States and other parts of the world. We report on the Johns Hopkins Clinical Research Network (JHCRN), established in 2009 as a multi‐disease research collaboration between the academic medical centers and community hospitals/health systems. We have discussed vision, governance, infrastructure, participating hospitals' characteristics, and lessons learned in creating this partnership. Designed to leverage organized patient communities, community‐based investigators, and academic researchers, the JHCRN provides expedited research across nine health systems in the mid‐Atlantic region. With one IRB of record, a centralized contracting office, and a pool of dedicated network coordinators, it facilitates research partnerships to expand research collaborations among the differing sizes and types of hospitals/health systems in a region. As of August 2024, total 81 studies‐clinical trials, cohort studies, and comparative effectiveness research have been conducted, with funding from the NIH, private foundations, and industry. The JHCRN experience has enhanced understanding of the complexity of participating sites and associated ambulatory practices. In conclusion, the CRN, as an academic–community partnership, provides an infrastructure for multiple disease studies, shared risk, and increased investigator and volunteer engagement.